Pemberdayaan Masyarakat dalam Mewujudkan Desa Sadar Hukum untuk Menciptakan Ketertiban Masyarakat, dan Peningkatan Perekonomian di Kecamatan Kampar Kabupaten Kampar - Andrikasmi, Sukamarriko; Firdaus, Emilda; Musliadi, Ricki; Zulhidayat, Muhammad (Unri Conference Series: Community Engagement, 2024)
A legally aware village is a form of orderly and obedient society from the lowest level, so that it will further increase compliance with applicable laws and regulations. It is considered more appropriate for villages to empower the community so that a village will be aware of the law. This empowerment was carried out in Batu Belah village, Naumbai village and Ranah Baru village, Kampar District, Kampar Regency. The aim of this empowerment is to increase legal awareness and improve the economy of the community in the village so that the village can be more advanced than before and more prosperous. This activity is carried out through legal outreach, training and assistance which includes techniques for drafting village regulations, and legal assistance. The method used is a participatory approach, where the community is actively involved in every stage of the activity. The results of this service show an increase in community knowledge about the village's readiness to be aware of the law. This effort not only aims to create order and security, but also to improve the local economy. With collaboration between the government, community and the private sector, it is hoped that Batu Belah Village, Naumbai Village and Ranah Baru Village can become models for other villages in integrating legal awareness with sustainable economic development, so that community welfare can be realized as a whole.